ORGAN DONATION AND TRANSPLANTATION IN THE RUSSIAN FEDERATION IN 2014 7th REPORT OF NATIONAL REGISTER - S. V. Gautier; Ya. G. Moysyuk; S. M. Khomyakov (Вестник трансплантологии и искусственных органов, 2015)
Aim. To carry out monitoring of the organization and development of organ donation and transplantation in the Russian Federation according to 2014. Materials and methods. Questioning of heads of all the centers of transplantation is carried out. The comparative analysis of the obtained data in dynamics of years, between certain regions of the Russian Federation, the transplantation centers, and also with data of the international registers is made. Results. According to the Register in 2014 in the Russian Federation functioned 36 centers of kidney transplantation, 14 centers of liver transplantation and 9 centers of heart transplantation. The waiting list of kidney transplantation in 2014 included 4636 potential recipients that makes 16% of total number of the patients 29 000 receiving dialysis. The rate of donor activity in 2014 made 3.2 per million population (pmp). Efficiency of donor programs in 2014 continued to increase: the share of effective donors after brain death in 2014 increased to 77.2%, the share of multiorgan explantation made 50.5%, average number of organs received from one effective donor made 2.6. In 2014 the rate of kidney transplantation made 7.0 pmp, the rate of liver transplantation made 2.1 pmp and the rate of heart transplantation made 1.1 pmp. In the Russian Federation the number of transplantations of liver and heart continues to increase. The significant contribution to development of the organ donation and transplantation brings the Moscow region in which 11 centers of transplantation function and nearly a half from all kidney transplantations and more than 65% of all liver and heart transplantations are carried out. Conclusion. In theRussian Federation the potential for further development of the transplantology remains. In particular, at the expense of increase in the efficiency of regional donation programs, introduction of technologies, expansion of the practices of multiorgan donation and transplantations of extrarenal organs, interregional transplant coordination. Preservation of volumes of public funding for transplantological medical care and federal financing of donation programs in regions are of great importance.